1992
DOI: 10.1161/01.res.71.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cardiac calcium release channel (ryanodine receptor) expression in myocardium from patients with end-stage heart failure caused by ischemic versus dilated cardiomyopathy.

Abstract: The molecular basis for the systolic and diastolic dysfunction characteristic of end-stage heart failure in humans remains poorly understood. It has been proposed that both abnormal calcium handling and defects in the contractile apparatus may contribute to the myocardial dysfunction. Two channels, the calcium release channel (CRC) or ryanodine receptor of the sarcoplasmic reticulum (SR), and the slow calcium channel or dihydropyridine receptor (DHPR) of the transverse tubule, play key roles in regulating intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
51
0
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(61 citation statements)
references
References 39 publications
(4 reference statements)
7
51
0
2
Order By: Relevance
“…25 RyR2 is downregulated in experimental heart failure in dogs, 25,26 and the RyR2 protein and mRNA levels are also subnormal in failing human myocardium. 27 Our data suggest that FPVT is a disease showing close kinship to malignant hyperthermia and central core disease, which are rare, dominantly inherited disorders of calcium signaling in striated muscle resulting from mutations of the RyR1 gene. 28,29 Malignant hyperthermia is characterized by skeletal muscle rigidity and contractures, malignant cardiac arrhythmias, hypermetabolism, and eventually fever, which is typically triggered by the administration of halothane or depolarizing skeletal muscle relaxants.…”
Section: Discussionmentioning
confidence: 69%
“…25 RyR2 is downregulated in experimental heart failure in dogs, 25,26 and the RyR2 protein and mRNA levels are also subnormal in failing human myocardium. 27 Our data suggest that FPVT is a disease showing close kinship to malignant hyperthermia and central core disease, which are rare, dominantly inherited disorders of calcium signaling in striated muscle resulting from mutations of the RyR1 gene. 28,29 Malignant hyperthermia is characterized by skeletal muscle rigidity and contractures, malignant cardiac arrhythmias, hypermetabolism, and eventually fever, which is typically triggered by the administration of halothane or depolarizing skeletal muscle relaxants.…”
Section: Discussionmentioning
confidence: 69%
“…13,15,[19][20][21][22][23] Along with this depression in SERCA 2 pump protein it was shown that in failing hearts, where the severity of failure was assessed by ventricular ANF mRNA levels, there is a correlation among SERCA2 calcium pump ATPase, phospholamban as well as ryanodine receptor mRNA (Figure 8). 11) Thus it would appear that in failing hearts all of the sarcoplasmic reticular calcium cycling proteins are down regulated and this observation has been supported by a number of additional measurements 21,24,25) (Figure 9). In contrast to the down regulation of the calcium cycling proteins in the sarcoplasmic reticulum, there is an up regulation of the sarcolemmal sodiumcalcium exchange protein where the mRNA level normalized for 18S mRNA and the protein normalized per myosin heavy chain is increased by 83 % (p < 0.05) and 85 % (p < 0.05), respectively 17) (Figure 9).…”
Section: )mentioning
confidence: 79%
“…16,30 In failing human hearts, RyR2 mRNA level is decreased in various types of cardiopathies 31 but unchanged in dilated cardiopathy. 32 Decrease in ryanodine receptor mRNA level is correlated with decreased SERCA 2 and phospholamban mRNA levels, suggesting that these genes are coordinately regulated and that they are inversely correlated to the level of ANF 20 and IP 3 R mRNAs. 31 In contrast, RyR2 protein level and the number of high-affinity Ryanocline binding sites were similar in nonfailing and failing human hearts.…”
mentioning
confidence: 99%
“…31 In contrast, RyR2 protein level and the number of high-affinity Ryanocline binding sites were similar in nonfailing and failing human hearts. 32 Thus, as for SERCA 2, data concerning the expression of RyR2 in human cardiopathy are conflicting. In animal models, however, severe compensated hypertrophy is generally associated with a decrease in the expression of SERCA 2 and RyR2.…”
mentioning
confidence: 99%